Democratização do Poder Judiciário: a ouvidoria do Conselho Nacional de Justiça como instrumento de participação popular - Ronaldo Araújo Pedron (2017)
According to the principle of popular sovereignty and active citizenship present in the democratic state of law, regulated in the Federal Constitution unequivocally 1988 and a series of infra-constitutional normative, what we see is a growing discussion about the real capacity of various groups and organized or no transactions are recognized (and recognize) as actors and authors, either directly or represented way in decision-making of policies, as well as throughout your cycle, from deliberation, formulation, monitoring and evaluation of public policies. Foundational aspect of this issue refers to the strict relationship between the legitimacy of government actions, not only by the match results (expected or achieved) and the objectives of certain government programs, but especially by the degree of influence or participation of civil society organizations, or even individuals. If the discussion on participatory democracy and its legitimacy deficits show is still very relevant and current in relation to the legislative and executive branches, what of participatory democracy in the judiciary? A power recognized for being traditionally tight, closed, and that often, sought the principle of "fairness" grounds for that distance. How to make your operation more intelligible grammar and its more permeable citizen management? How to put it, the light control and participation needed in a participatory democracy, the scrutiny of the population. These concerns are the leitmotif of the proposed project. glimpsed here a mediation role to be played by the Ombudsman, to act as a means for dialogue between citizens and the organs of justice, aimed at finding solutions that are, to the organs involved, achievable, and that meet the interests of the citizen and society. Institutional and normatively, this task is assigned to the judicial ombudsman, who identify with the primary locus of citizen dialogue with the administration of justice. But the central question lies in checking whether and how this role has been played. And what is the potential to, in Bonaventure's sayings, they constitute democratic mechanisms (otherness) of the Judiciary. And how dialogically this discussion or construction settle, not only new rights but also the very notion of emancipation, citizenship and social justice.